Analysing the relevance of public service broadcasting in the South African television sector for the digital dispensation - Gongxeka, Nomonde (My University, 2016)
In the current era of the digital television (TV) broadcasting dispensation, the relevance of the Public Service Broadcasting (PSB) mandate in South Africa remains critical, to inform and build democracy in the public interest. Recent debates with regard to the relevance and retention of PSB in the digital era seem to suggest that there are divergent views in this regard. These debates gave rise to this study. The study aimed to assess and reconfigure the role of the South African Broadcasting Corporation (SABC) in carrying the public broadcasting mandate in the digital era. Furthermore, the study explored how the PSB remit can be repositioned to meet the needs of South African citizens in the 21st century. In addition, this study investigated the evolution of public service broadcasting policy and the role played by the Department of Communications (DoC), the policy maker in informing policy. The study seeks to ascertain whether the policy direction provided by the DoC is in actual fact in sync with the developments taking place in the TV broadcasting sector. This research followed a qualitative research approach, by exploring the relevance of PSB in the digital era and also by examining South Africa’s 3-tier broadcasting system, with a particular focus on the SABC. The research analysed the SABC (PSBs), MultiChoice (pay-TV licensee), e.tv (Free-to-Air commercial licensee) and Association of Community Television in South Africa (ACT-South Africa), a body representing Community TV licensees, in their attempts to discharge the PSB remit in the digital era. The qualitative paradigm aided in the process of describing and understanding the research topic. The main findings of this study revealed that the PSB mandate still has relevance in the digital era, however weak this may be. The multi-channel and the competitive TV broadcasting landscape will deplete the commercial advertising market share, on which the SABC heavily relies for revenue income. Secondly, the SABC’s mandate can never be upheld unless appropriate funding is secured by government. Lastly, the findings reveal that the DoC has regressed in providing policy and prescriptions and that there is thus a policy vacuum in the implementation of the PSB mandate.
A research report submitted to the Faculty of Humanities, of the University of Witwatersrand, in partial fulfilment of the requirements for the Degree of Master of Arts in ICT Policy and Regulation October 2016
Keywords: Public broadcasting--South Africa; Broadcasting policy--South Africa; Television broadcasting--South Africa; Digital television--South Africa